2023
DOI: 10.1186/s12886-023-03123-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of brittle cornea syndrome by multimodal imaging modalities: a case report

Huixian Wang,
Xu Zhang,
Xiaowei Gao
et al.

Abstract: Background A report of a Brittle cornea syndrome (BCS) case with bluish scleral discoloration, keratoglobus, and myopia based on multimodal imaging modalities including in vivo confocal microscopy (IVCM), high-definition optical coherence tomography (HD-OCT) and scheimpflug corneal densitometry analysis. Case presentation A 36-year-old Chinese female patient presented with significant bluish discoloration of the sclera in both eyes, extreme corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…BCS patients often present with a thin, spherical cornea and scleral discolouration [ 10 , 11 ]. In addition, some patients may be complicated with other systemic symptoms, such as frequent fractures and excessive flexion and extension of the joints [ 5 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCS patients often present with a thin, spherical cornea and scleral discolouration [ 10 , 11 ]. In addition, some patients may be complicated with other systemic symptoms, such as frequent fractures and excessive flexion and extension of the joints [ 5 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, Wan et al reported the case of a 6-year-old girl with blue sclera and extreme corneal thinning with anterior corneal protrusion who was diagnosed with BCS [ 16 ]. Wang et al reported a 36-year-old Chinese female patient presented with significant bluish discolouration of the sclera in both eyes, extreme corneal thinning with increased corneal curvature, increased central corneal densitometry, scoliosis, severe osteoporosis, and thyroid disease [ 11 ]. Neither of these studies conducted further analyses of the types of mutations that might be present.…”
Section: Discussionmentioning
confidence: 99%